Resolution of anuric acute kidney injury in a dog with multiple organ dysfunction syndrome. (6th November 2014) - Hoareau, Guillaume L.; Epstein, Steven E.; Palm, Carrie; Ybarra, Winnie; Jandrey, Karl E.; Cowgill, Larry D.
Abstract Objective To describe the management and resolution of anuric acute kidney injury (AKI) in a dog with multiple organ dysfunction syndrome (MODS) associated with gallbladder wall necrosis. Case Summary An 11‐year‐old neutered female spayed dog was referred for evaluation of anuria following cholecystectomy. Following surgery, the patient became anuric with no response to appropriate medical therapy. During the course of hospitalization, the patient developed MODS as evidenced by alteration in renal function, but also cardiovascular dysfunction, coagulation disorders, and hypoglycemia. Several hemodialysis treatments were performed and, along with intensive care, led to resolution of clinical signs and return of urine production. New or Unique Information This report describes resolution of anuria in a dog with AKI and MODS. In this clinical setting, despite a poor prognosis, survival and recovery of adequate renal function were possible with medical management that included hemodialysis.